2017
DOI: 10.5488/cmp.20.13003
|View full text |Cite
|
Sign up to set email alerts
|

Geometric characteristics of quantum evolution: curvature and torsion

Abstract: We study characteristics of quantum evolution which can be called curvature and torsion. The curvature shows a deviation of the state vector in quantum evolution from the geodesic line. The torsion shows a deviation of state vector from the plane of evolution (a two-dimensional subspace) at a given time.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Such evolution, Eq. (45), proceeds precisely along the geodesic determined by the Fubini-Study metric [19,38], saturating the Mandelstam-Tamm bound [39]…”
Section: Discrete History Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such evolution, Eq. (45), proceeds precisely along the geodesic determined by the Fubini-Study metric [19,38], saturating the Mandelstam-Tamm bound [39]…”
Section: Discrete History Statesmentioning
confidence: 99%
“…The latter vanishes just for the geodesic evolution, where ∆H = ∆H min = φ t f σ y and hence (∆H min ) 4 = (∆H min ) 2 2 = φ 4 /t 4 f , implying E 2 (S, T ) = E min 2 (S, T ). Such fluctuation represents a curvature coefficient which measures the deviation from the geodesic [38,40].…”
Section: Discrete History Statesmentioning
confidence: 99%
“…To begin, we observe that the path γ t traced by the state vector |ψ(t) = cos t |A + sin t |B is a geodesic path. Indeed, a simple calculation shows that |ψ(t) can be recast as a quantum geodesic line [20]:…”
Section: Time-independent Scenariomentioning
confidence: 99%
“…The concept of a distance between quantum states in Hilbert space [1][2][3] has found its application in different fields of quantum mechanics related to the evolution of quantum systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], quantum entanglement [8,[20][21][22][23][24][25][26][27][28][29][30], quantum computations [31][32][33][34][35], etc. It was shown that the distance, which the quantum system passes during the evolution in the Hilbert space, is related to the integral of the uncertainty of energy that in turn defines the speed of evolution [4].…”
Section: Introductionmentioning
confidence: 99%